2021
DOI: 10.1177/08948453211037011
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Career Construction Model of Adaptation Among Filipino Senior High School Students

Abstract: Career development literature that tested the career construction model of adaptation has, thus far, examined adaptability resource as a mediator in the relationship between adaptive readiness and adaptation results; however, there remains a need to elaborate the links between adaptive resources, adapting response, and adaptation results. This research tested a path model among 331 Filipino senior high school students using hope, career adaptability, career engagement, and life satisfaction as measures of adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 53 publications
(103 reference statements)
2
10
0
Order By: Relevance
“…Guan et al, 2014; Šverko & Babarović, 2018; Zhuang et al, 2018). However, these results support those of previous cross-sectional studies based on students (e.g., Ochoco & Ty, 2021; Öztemel & Yıldız-Akyol, 2020) and working adults (e.g., Tokar et al, 2020). These cross-sectional studies have indicated that the indirect effect of adaptive readiness on adaptation results was significant via the combination of adaptability and adapting responses.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Guan et al, 2014; Šverko & Babarović, 2018; Zhuang et al, 2018). However, these results support those of previous cross-sectional studies based on students (e.g., Ochoco & Ty, 2021; Öztemel & Yıldız-Akyol, 2020) and working adults (e.g., Tokar et al, 2020). These cross-sectional studies have indicated that the indirect effect of adaptive readiness on adaptation results was significant via the combination of adaptability and adapting responses.…”
Section: Discussionsupporting
confidence: 90%
“…A four-wave design has also been used to test three of its components (Green, 2021a). It is also relevant to mention here that this is among the sparse studies to test the full sequence of its four components (e.g., Guan et al, 2014; Merino-Tejedor et al, 2016; Ochoco & Ty, 2021; Öztemel & Yıldız-Akyol, 2020; Perera & McIlveen, 2017; Šverko & Babarović, 2018; Tokar et al, 2020; Zhuang et al, 2018). Lastly, to the best of our knowledge, there is practically no research on vocational psychology from Afghanistan.…”
mentioning
confidence: 99%
“…Third, we also contribute to integrating research on career construction theory with the sustainable career framework by revealing the linkage between the career construction model of adaptation and career sustainability. In addition, past studies used CCMA as a theoretical framework designated adaptation results with well-being (Tokar et al, 2020), happiness ( € Oztemel and Akyol, 2021), life satisfaction (Ochoco and Ty, 2021), academic satisfaction (Nilforooshan, 2020) and employment (Guan et al, 2014). In the current study, we used career sustainability as an indicator for adaptation results, a composite indicator of health, happiness, and productivity.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…While recent studies used CCMA as a theoretical framework partially and more often on student populations (e.g. Nilforooshan, 2020;Ochoco and Ty, 2021;€ Oztemel and Akyol, 2021), this study tests the complete model on full-time working professionals to advance its applicability from entry-level career issues to subsequent career development and sustainability challenges.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…It denotes coping behaviors (Savickas, 2013). In the literature, career engagement is measured as adapting responses (e.g., Nilforooshan & Salimi, 2016;Ochoco & Ty, 2021). In the present study, career engagement was used to measure adapting responses.…”
Section: Proactive Career Behaviors (Pcb) As An Indicator Of Adapting...mentioning
confidence: 99%